A Review of Treatment of Coronavirus Disease 2019 (COVID-19): Therapeutic Repurposing and Unmet Clinical Needs - Chen, Po-Lin; Lee, Nan-Yao; Cia, Cong-Tat; Ko, Wen-Chien; Hsueh, Po-Ren (Frontiers in Pharmacology, 2020)
For the initial phase of pandemic of coronavirus disease 2019 (COVID-19), repurposing drugs that in vitro inhibit severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) have been attempted with overlooked or over-estimated efficacy owing to limited clinical evidence. Most early clinical trials have the defects of study design, small sample size, non-randomized design, or different timings of treatment initiation. However, well-designed studies on asymptomatic or mild, or pediatric cases of COVID-19 are scarce and des-perately needed to meet the clinical need. However, a trend could be ob-served based on current clinical evidence. Remdesivir and favipiravir may shorten the recovery time; lopinavir/ritonavir does not demonstrate treatment efficacy in severe patients. Triple therapy of ribavirin, lopinavir, and interferon β-1b showed early viral negative conversion, and the major effect may be re-lated to interferon. Some small sample-size studies showed that interleukin-6 inhibitors may demonstrate clinical improvement; non-critical patients may benefit from convalescent plasma infusion in small sample-size studies; and the role of hydroxychloroquine or chloroquine in the treatment and prophylaxis of COVID-19 remains unclear. Combination therapy of traditional Chinese medicine with antiviral agents (ex. interferon, lopinavir, or arbidol) may allevi-ate inflammation in severe COVID-19 patients based on small sample-sized observational studies and experts’ opinion. Most of the published studies in-cluded severe or critical patients with COVID-19. Combination therapy of anti-viral agents and immune-modulating drugs is reasonable especially for those critical COVID-19 patients with cytokine release syndrome. Drugs to blunt cy-tokine release might not benefit for patients in the early stage with mild dis-ease or the late stage with critical illness. Traditional Chinese medicine with antiviral effects on SARS-CoV-2 and immune-modulation is widely used for COVID-19 patients in China, and is worthy of further studies. In this review, we aim to highlight the available therapeutic options for COVID-19 based on current clinical evidence and encourage clinical trials specific for children and for patients with mild disease or at the early stage of COVID-19.